Current and future development of nanocarbon and its biocomposites production - Mohammed Mahbubul, Matin; Mohammad, Amran; Md. Badrul, Islam; Mohin, Hasnain; Sayeda Halima, Begum; Md Rezaur, Rahman; Md. Abdul Majed, Patwary; Muhammad Khusairy, Bakri (Woodhead Publishing / Elsevier Ltd., 2024)
The valence layers of carbon contain four electrons. Carbon has the remarkable capacity to arrange these four valence electrons in various hybridization states, forming both strong covalent and weak π-π-bonds. It is simple to polymerize into long-chained molecules with a high molecular weight. It is able to link with almost all chemical elements (both metals and nonmetals) due to its distinctive electrical structure and smaller size compared to group IV. Because of this, carbon-based compounds can exist in a variety of molecular configurations, and the same type of atoms can be arranged in various shapes with various orientations known as allotropes (e.g., graphite and diamond). With the aid of these properties, carbon can produce a variety of nanostructures, including mono- and multiwalled carbon nanotubes (MWCNTs), carbon fibers, fullerenes, onions, and nanodiamonds.